Minimum Number of Si-C Bilayers Needed in Polytypes of SiC Semiconductor to Exhibit Bandgaps of Bulk Materials - Chanana, Ravi Kumar (Transactions on Engineering and Computing Sciences, 2023)
In this short research article, the minimum number of Si-C bilayers needed in polytypes of SiC semiconductor are calculated, such that the semiconductor materials exhibit bandgap of bulk materials.